Has green innovation in marine-related enterprises reduced environmental pollution? –a perspective based on executives’ environmental awareness - Wang, Changrong; Dong, Xiaopeng (Frontiers in Marine Science, 2024)
This study investigates the direct impact of green innovation in marine-related enterprises on pollution emissions, addressing a significant gap in existing research regarding the role of executives' environmental awareness factor. Using a sample of 2,580 marine-related firm-year observations from the 2008-2022 period, we find that green innovation and improved environmental awareness among management can significantly reduce water pollution and air pollutants in enterprises and reduce the environmental problems caused by marine-related businesses. Moreover, enhancing environmental awareness within management can effectively substitute for the inhibitory effects of green innovation on pollution emissions. We conduct a heterogeneity test, and it proves that the inhibitory effects of green innovation and executives' environmental awareness vary across industries and ownership types. These findings contribute to the literature on the sustainable development of marine enterprises.